Pengembangan Aplikasi Permainan Self-Confidence Book untuk Meningkatkan Self-Confidence pada Anak Tunagrahita - Devira Putri Giana; Citra Novita Nur Amalia (Jurusan Pendidikan Luar Biasa Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2020)
The purpose of this study is to increase self-confidence in mentally retarded children who are designed using an application-based self-confidence book so as to provide attraction to the mentally retarded child. The method used in this study is the study of literature by examining 8 journals related to the self-confidence book (busy book) game. The literature review results that have been reviewed are used to develop this research related to application-based self confidence book games for mentally retarded children.The results showed that of 30 mentally retarded children in the intervention group before being given a game showed 16 children experienced insecurity with an average of 2.13, while in the control group showed 18 children experienced insecurity with an average of 1.73. After being given a game in the intervention group showed 14 children experienced self-confidence with an average of 3.20 while in the control group showed 17 children experienced self-confidence with an average of 1.70. There was an increase in the average self-confidence of mentally retarded children before and after the game was given with an average of 2.13 before the intervention and 3.20 after the intervention was given to the intervention group.